Concrete Homes in the Arctic Wasteland. Reconstructing and Reinventing Nuuk’s boligblokke in Danish Literary Fiction about Greenland - Turri, Francesca (Folia Scandinavica Posnaniensia, 2025)
Nuuk, the capital of Greenland, occupies a unique place in contemporary Danish-language literature as both a modern Nordic city and a site marked by colonial history. This urban setting is a common feature of Lotte Inuk’s Sultekunstnerinde (2004) and Mads Peder Nordbo’s Pigen uden hud (2017). Through a close reading of significant passages from the two books, respectively a young adult novel with a clear autofictional component and an ‘Arctic noir’, I will focus on the architecture of (literary) Nuuk, with particular attention to a specific and ‘uncanny’ type of building: the characteristic concrete boligblokke built in the years of the so-called modernization, symbol of the centralization policies favored by Denmark starting from the 1950s. In Sultekunstnerinde, these buildings are ‘reconstructed’ and presented to the reader as places of childhood, while a recurring setting in Pigen uden hud is the controversial Blok P – which, in the fiction of the novel, is ‘reinvented’ as the setting of brutal murders of its inhabitants. The emphasis on spatiality and architecture, given the symbolic significance of these buildings, will be combined with a postcolonial reading.